AI-22 Single cell protein and transcriptional profiling of CD4+ follicular B helper T (TFH) and central memory (TCM) cells in SLE: physiological and pathological phenotypes. (31st August 2016) - Kwak, Minsuk; Choi, Jin-Young; Kim, Seewan; Chen, Zhuo; Lee, Geehee; Craft, Joe; Fan, Rong
Abstract : Background: Follicular B helper T (Tfh) cells expand in the circulation of patients with systemic lupus erythematosus and are correlated with pathological outcomes (Choi, et al., Arthritis Rheum. 2015). These cells are both necessary and sufficient to drive pathogenic humoral autoimmunity in murine lupus, and likely in SLE. Materials and methods: We performed multidimensional single cell secretome profiling on Tfh cells from patients with SLE and controls, in parallel with transcriptome (RNA-seq) analysis (including single cell) of Tfh and central memory (Tcm) cells. Results: We find that single Tfh and Tcm cells in SLE are polyfunctional cytokine producers, for example, co-secreting both B-helper IL-21 and inflammation-inducing IFN-γ in excess of that seen in controls. Given their pathogenic potential in lymphoid organs and in disease-affected end organs, such as the lupus kidney, and to dissect the mechanisms underlying the aberrant secretome phenotypes, we performed transcriptome (RNA-seq) analysis (including single cell) of Tfh and central memory (Tcm) cells from SLE patients and healthy donors. Principal component analysis (PCA) of single-cell transcriptomes was done using the top 2000 differentially expressed genes based on ANOVA-testing, revealing four distinct clusters of Tfh and Tcm cells, separating cells from healthy donors and SLE patients. Pathways determined by gene ontology (GO) and pathway enrichment analysis that were highly enriched in SLE T cells included mediators of adaptive responses and inflammation, and those regulating co-stimulation. By contrast, negative regulators of cell proliferation and function were found in the healthy control cluster, and diminished in SLE. Conclusions: Our data demonstrate altered transcriptional programs of lupus Tfh and Tcm cells, and therapeutic targets in disease. They also represent the first detailed transcriptional profiling, and single cell transcriptional profiling, of Tfh cells, the necessary and critical driver of humoral immunity in SLE. Acknowledgements: Supported in part by grants from the NIH/NIAMS (AR40072 and AR053495) and from the Alliance for Lupus Research (to JC).